Human Security and Development at the Border: the Case of Ba’kelalan, Sarawak, Malaysia - Yusten Karulus; Kamarulzaman Askandar (Springer link, 2020)
This study examines the causal relationship between development and human security at the border. In Malaysia, among the main goals in implementing development policies include ensuring prosperity as well as human security of its citizens. However, the effectiveness of these policies, particularly in the context of border communities living in the interior, is largely unknown. Accordingly, research has conducted interviews and observations at the border area of Ba’kelalan, Sarawak, Malaysia, to assess (1) the impact of Malaysian development policies on the socioeconomic status and international cross-border dimension and (2) the extent to which developmental issues have posed a threat to the human security at the border. Research found that although Malaysian development policies have succeeded to bring various development programs in Ba’kelalan, it has inadequately addressed some developmental issues in this area. The reality of development inequality, lack of development in the agricultural sector, and the ambiguous status of lands are found to have threatened human security of the Lun Bawang in Ba’kelalan. If the goal is promoting people-centered security and responding to the core objective of human security to prioritize risk prevention and early intervention of the human security threat, understanding the reality experienced by the people on the ground and considering views from the bottom in the national policy decision and formulation in the future are crucial.